Neural Responses to Implicit Forms of Peer Influence in Young Adults - Venticinque, Joseph S. (Soc Neurosci, 2021)
Young adults are acutely sensitive to peer influences. Differences have been found in neural sensitivity to explicit peer influences, such as seeing peer ratings on social media. The present study aimed to identify patterns of neural sensitivity to implicit peer influences, which involve more subtle cues that shape preferences and behaviors. Participants were 43 young adults (M(Age) = 19.2 years; 24 males) who underwent functional magnetic resonance imaging while completing a task used to assess neural responses to implicitly “socially tagged” symbols (previously judged by peers as liked vs. not liked, thus differing in apparent popularity) vs. novel symbols that carried no social meaning (not judged by peers). Results indicated greater activity in brain regions involved in salience detection (e.g., anterior cingulate cortex) and reward processing (e.g., caudate) to socially tagged vs. novel symbols, and particularly to unpopular symbols. Greater self-reported susceptibility to peer influence was related to more activity in the insula and caudate when viewing socially tagged vs. novel symbols. These results suggest that the brain is sensitive to even subtle cues varying in level of peer endorsement and neural sensitivity differed by the tendency to conform to peers’ behaviors particularly in regions implicated in social motivation.